Anwar Ibrahim Tenacious in Dissent, Hopeful in Power - Khoo, Boo Teik (Strategic Information and Research Development Centre, 2023)
Over 50 years Anwar Ibrahim was a Malay nationalist student, a motor of Islamic activism, a co-opted rising star in government, an 'anointed successor' to the premiership, a persecuted reformist, and a revitalized Opposition Leader. He disdained comfortable irrelevance to rouse indignant masses against the regimes of five prime ministers. In September 1998 he was a political prisoner with a blackened eye. In November 2023 he became the Prime Minister. In the 21st century his anti-corruption campaigns fought ruling power structures that fused state, regime and party. His politics used his charismatic and chameleonic personality, and his complex ideas on Islam, a humane economy, coalition politics, and a reimagination of society. He outmanoeuvred his influential ethno-religious opponents through a parlous condition of Malay politics, and now leads a large Unity Government of which the deposed hegemon, UMNO, is only a subordinate partner. This book explores how a tenacious but hopeful Anwar seeks to transform society at an unsteady moment of Malaysian politics.